2020
DOI: 10.1016/j.ebiom.2020.102735
|View full text |Cite
|
Sign up to set email alerts
|

Systemic enzyme delivery by blood-brain barrier-penetrating SapC-DOPS nanovesicles for treatment of neuronopathic Gaucher disease

Abstract: Background: Enzyme replacement therapy (ERT) can positively affect the visceral manifestations of lysosomal storage diseases (LSDs). However, the exclusion of the intravenous ERT agents from the central nervous system (CNS) prevents direct therapeutic effects. Methods: Using a neuronopathic Gaucher disease (nGD) mouse model, CNS-ERT was created using a systemic, non-invasive, and CNS-selective delivery system based on nanovesicles of saposin C (SapC) and dioleoylphosphatidylserine (DOPS) to deliver to CNS cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 70 publications
0
21
0
Order By: Relevance
“…Neoplastic cells are predicted to be sensitive to cytotoxicity of the saposin-fat complexes. As a membrane-associated protein, SapC can tightly bind the negatively charged phospholipids (DOPS) to form a stable and pharmacologic active nanovesicle, SapC-DOPS [ 115 , 116 ]. This “nanodrug” selectively targets phosphatidylserine, a surface lipid biomarker on tumor cells and vessels [ 117 , 118 ].…”
Section: Targeting a Phospholipid With A Saposin C Embedded Nanopamentioning
confidence: 99%
See 2 more Smart Citations
“…Neoplastic cells are predicted to be sensitive to cytotoxicity of the saposin-fat complexes. As a membrane-associated protein, SapC can tightly bind the negatively charged phospholipids (DOPS) to form a stable and pharmacologic active nanovesicle, SapC-DOPS [ 115 , 116 ]. This “nanodrug” selectively targets phosphatidylserine, a surface lipid biomarker on tumor cells and vessels [ 117 , 118 ].…”
Section: Targeting a Phospholipid With A Saposin C Embedded Nanopamentioning
confidence: 99%
“…Tumor-specific cytotoxicity of SapC-DOPS on a variety of cancer types leads to apoptotic and lysosomal cell death, thus inhibiting tumor growth and improving survival of tumor-bearing animals [ 119 , 120 ]. SapC-DOPS has been previously studied in pancreatic, lung, pediatric, and other brain tumors [ 116 ]. As for suggesting its use in the GBM space, SapC-DOPS penetrates the BBB and BTB to regress brain tumors in mice [ 116 , 121 ].…”
Section: Targeting a Phospholipid With A Saposin C Embedded Nanopamentioning
confidence: 99%
See 1 more Smart Citation
“…SapC-DOPS-GCase-containing nanovesicles were able to penetrate through BBB via the surface phosphatidylserine. These vesicles also led to a reduction of GCase substrate levels, attenuating brain inflammation (Sun et al, 2020 ).…”
Section: Therapeutic Strategies Potentially Targeting Cns Manifestatimentioning
confidence: 99%
“…A synergistic effect of SapC-DOPS and TMZ has been demonstrated for GBM in mice [ 31 ]. In addition, we have recently demonstrated that SapC-DOPS can cross the BBB to deliver a deficient enzyme and effectively treat a mouse model of Gaucher disease [ 32 ]. Importantly, we have recently demonstrated that radiation increases surface PS on a variety of cancer cells and that this enhances the killing of the cells by SapC-DOPS both in vitro and in subcutaneous tumors in a combination therapeutic approach [ 33 ].…”
Section: Introductionmentioning
confidence: 99%